Evaluation and predictive factors analyses for patient-self-reported depression, anxiety and quality of life in patients with metastatic renal cell carcinoma underwent interferon-α treatment: a prospective cohort study - Wang, Yanjie; Song, Bingbing; Zhang, Yuling; Li, Haibo (Translational Cancer Research, 2018)
Background: This study aimed to investigate the patient-self-reported depression, anxiety and quality of life (QoL) as well as their predictive factors in patients with metastatic renal cell carcinoma (mRCC) underwent interferon-alpha (IFN-α) treatment. Methods: A total of 127 patients with mRCC underwent IFN-α treatment were consecutively enrolled in this prospective cohort study. Anxiety, depression and QoL were assessed at week 0 (W0), W4, W8 and W12 by Hospital Anxiety and Depression Scale (HADS) and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30 Scale), respectively. Results: The percentages of anxiety and depression both increased at W12 compared with W0. The EORTC QLQ-C30 Scale-Global health status score, EORTC QLQ-C30 Scale-Function and EORTC QLQ-C30 Scale-Symptoms scores did not deteriorate at W4, W8 or W12 compared with W0. Multivariate logistic regression analyses revealed that older age and elevated level of highest education independently predict reduced risk of HADS-Anxiety score elevation at W12, while hypertension was an independent predictive factor for increased risk. Older age also independently associated with less risk of elevated HADS-Depression score. Smoke, hypertension, diabetes and higher ECOG performance were independent predicting factors for escalated risk of EORTC QLQ-C30 Scale-Global health status score elevation at W12, and higher ECOG performance was an independent predicting factor for increased risk of elevated EORTC QLQ-C30 Scale-Function score at W12. Conclusions: In conclusion, anxiety and depression increased while QoL did not deteriorate in mRCC patients during IFN-α treatment, and age, highest education, hypertension, smoke, diabetes as well as higher ECOG performance status correlated with their aggravation.